Investigating the impact of CALL on EFL students' speaking skills at Islamic boarding school: A mix-method approach - Nona Safira Timur; Slamet Asari; Nirwanto Ma'ruf (Universitas Islam Negeri (UIN) Syekh Wasil, Kediri, Indonesia, 2025)
Despite the importance of speaking fluency and confidence in EFL learning, students with limited speaking opportunities, such as those in Islamic boarding schools, continue to face challenges in developing oral communication skills. This study examines the impact of computer-assisted language learning (CALL) on speaking fluency and confidence among EFL students at Al-Mizan Islamic Boarding School in Indonesia. A mixed-method approach was employed. The quantitative data were collected through pre-tests and post-tests (N=24), while the qualitative data were collected through interviews (N=5) and observations. Speaking fluency was measured based on speech flow, pace, continuity, naturalness, and intonation, while confidence was measured based on willingness to participate, composure, eye contact, vocal clarity, and engagement. Results revealed significant improvements, with the average fluency score increasing from 55.46 to 75.67 and the confidence score from 58.63 to 80.58 after an eight-week CALL intervention. Qualitative findings highlighted that CALL’s interactive features and real-time feedback supported students in improving their pronunciation and reducing speaking anxiety. This study demonstrates that CALL has the potential to transform traditionally teacher-centred instructions in the EFL contexts with limited speaking opportunities, such as Islamic boarding schools, into more interactive, learnercentred, and engagement-driven learning environments.